Noble‐Metal‐Free NiS/C3N4 for Efficient Photocatalytic Hydrogen Evolution from Water. Issue 12 (2nd December 2013) - Hong, Jindui; Wang, Yongsheng; Wang, Yabo; Zhang, Wei; Xu, Rong
Abstract The front cover artwork for issue 12/2013 is provided by the group of Rong Xu at the Nanyang Technological University in Singapore. The image shows how a photocatalyst based on earth‐abundant elements only can contribute to a sustainable society. The Full Paper itself is available on page 2263 (10.1002/cssc.201300647).